FIQH AL-HADITH PERSPECTIVES ON HANDSHAKING BETWEEN GENDERS IN SOCIAL - Miko, Setia (International Journal of Multidisciplinary Reseach, 2025)
This study examines the phenomenon of handshaking between men and women from the perspective of Fiqh al-Hadith. Handshaking (mushafahah) is widely practiced as a symbol of respect and social harmony, yet Islamic law presents differing views on its permissibility, particularly between individuals who are not mahram. Through a descriptive qualitative method and library research, this study analyzes classical and contemporary Hadith sources to contextualize legal rulings on this matter. The findings reveal that the majority of scholars prohibit such practices, grounding their arguments in Hadith traditions that emphasize safeguarding against temptation (fitnah). However, alternative scholarly opinions allow contextual interpretations, considering handshakes as social necessities in modern settings, including diplomacy and intercultural interaction. The analysis highlights the importance of integrating textual and contextual approaches in Hadith studies to balance religious principles with contemporary social realities. Thus, Fiqh al-Hadith provides not only a normative legal framework but also a methodological basis for reconciling tradition with evolving human interactions in social and state contexts.